2014
DOI: 10.1111/pme.12469
|View full text |Cite
|
Sign up to set email alerts
|

How Clinicians Use Prescription Drug Monitoring Programs: A Qualitative Inquiry

Abstract: Objectives Prescription drug monitoring programs (PDMP) are now active in most states to assist clinicians in identifying potential controlled drug misuse, diversion or excessive prescribing. Little is still known about the ways in which they are incorporated into workflow and clinical decision making, what barriers continue to exist, and how clinicians are sharing PDMP results with their patients. Design Qualitative data were collected through online focus groups and telephone interviews Setting Clinician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 11 publications
2
56
1
1
Order By: Relevance
“…In our previous focus groups with providers in nine states, 6 participants reported discussing worrisome PDMP profiles with patients in a variety of ways, we found similar results in our interviews with Oregon clinicians. Focus groups and surveys of clinician PDMP users identified experiences of both positive and negative patient responses to discussion of worrisome PDMP profiles, with some reporting patient anger or denial.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our previous focus groups with providers in nine states, 6 participants reported discussing worrisome PDMP profiles with patients in a variety of ways, we found similar results in our interviews with Oregon clinicians. Focus groups and surveys of clinician PDMP users identified experiences of both positive and negative patient responses to discussion of worrisome PDMP profiles, with some reporting patient anger or denial.…”
Section: Introductionsupporting
confidence: 80%
“…Prior focus group research with clinicians suggested that PDMP use might vary depending on whether the patient was a new or existing patient. 6 We designed the interview guide to explore this distinction and how it might affect clinical decisions, actions, and patient interactions. The interview guide is available in the appendix.…”
Section: Methodsmentioning
confidence: 99%
“…How this change affected prescribing clinicians is not yet clear, but other studies have described important communication between pharmacists and clinicians regarding PDMP findings. 11 Some states have mandated use of the PDMP in certain circumstances or by certain prescribers (eg emergency physicians), and some have mandated registration by all prescribers. 1 Though the impact of these mandates is not yet well-studied, our findings suggest they are likely to increase PDMP use.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, the ways in which PDMPs are used in clinical settings vary widely depending on the type of practice, specialty, patient population, and other factors such as patient satisfaction surveys. 23,24 A national survey of physicians who primarily practice emergency medicine that asked about their knowledge and use of PDMPs revealed that, although awareness was high (87.2%), only 50.6% had ever used their state's PDMP, of whom only 30% reported being regular users. Time and complexity required to access relevant information were barriers to PDMP use.…”
Section: Discussionmentioning
confidence: 98%